Portable Multifunction Tester Design to Check the Continuity of Wires and to Measure the Electrical Parameters. - Kunaraj, A.; Joy Mathavan, J.; Jayasekara, K.G.D.R. (Springer Nature Singapore, 2021)
The objective of this paper is to design a single device for checking the continuity of single wire and multi wired cables with ease, measurement of current and voltage in an electrical circuit and providing light to the experimentation area by a single device. The device is named as portable multifunction tester. The status of the errors found by this device appears on the LCD display for visual observation. Buzzers are also provided to indicate the errors by making identical sounds. This is a non-destructive testing mechanism because no need to unmount or break any circuit or structures to troubleshoot and rectify the error.
Keywords: Continuity checking of wires; VGA cable; RJ45 cable; Portable multifunction tester